SEPARATION OF SYNONYMS IN GRAMMAR - Suhad Sabah Abdul Qader (American Journals Publishing, 2024)
This research aims to study the topic of "Separation of Collocations in Arabic Grammar", by shedding light on the grammatical phenomenon related to the separation of collocated pairs in the Arabic language, such as the verb and the subject, the noun and the complement, and other collocates. The research deals with the concept of separation and its types from the grammatical and rhetorical aspects, and reviews the cases in which separation is permitted and others in which it is prohibited, with a focus on the rhetorical and grammatical implications that result from that.The descriptive analytical approach was adopted in reviewing grammatical examples from the Arab heritage, explaining how separation contributes to improving the linguistic structure and accurate expression. The research highlights the importance of taking into account grammatical and rhetorical rules in determining the appropriate type of separation, and its impact on the intended meanings.The results show that separation in the Arabic language depends on the type of collocates and the type of separator, which enhances understanding of the relationship between linguistic structures and meanings. The study recommends further research in this field to develop a methodology for analyzing linguistic structures in the Arabic language.
Keywords: Separation, collocates, separation of collocates, grammar